Jane says, an exhibition of works by Ann Shelton. Issue 1 (1st May 2019) - White, Amanda
Jane says is an exhibition of works by Ann Shelton, that opened at the Denny Dimin Gallery in New York City, in Spring 2019. Ann's sumptuous photographic portraits of botanic arrangements – arranged by the artist with an ikebana-like approach – present these contrivances in larger-than-life detail. Divorced from the domestic interior and titled both for the medicinal plants they feature and female archetypes, each botanic composition reveals an unexpected history of women's plant knowledge and its suppression. An accompanying performance – assembled and choreographed by the artist – is constructed from a tapestry of quotes, and stories about the properties of plants, their historic use as contraceptives, for fertility and abortion. These arrangements show the plants contorted into obedience, just as colonization sought to control and claim our natural world and fellow species, and suppress indigenous and women's botanic expertise. Now, we find ourselves at the brink of irreversible biodiversity loss and climate change, living in the era of the Anthropocene. Shelton's work provokes us to consider not only humanity's relentless depletion of the natural world, but the role women will play in a regenerative future.